The Role of Tax Law on Personal Income Tax on Tax Compliance - Andhi Ghani; Imam Adriansyah; Jihan Nabila; Sultan Khairul; Tanty Novianty (ISNU Sumatera Utara, 2025)
Tax law enforcement plays a strategic role in encouraging taxpayer compliance, particularly in the context of personal income tax. The objective of this study is to examine the extent of influence of tax regulations on improving individual taxpayer compliance. The normative legal approach is the research methodology used, accompanied by a qualitative review of literature, tax laws and regulations, and relevant taxpayer compliance data. Based on the research results, the main determinants of compliance are proportional sanctions, legal clarity, and an open tax administration system. Furthermore, the effectiveness of tax regulations in providing legal protection and fiscal justice also influences taxpayer perceptions of their tax obligations. The conclusion of this study confirms that strengthening tax regulations, both in terms of regulation and implementation, is crucial in creating a culture of tax compliance among individual taxpayers.